Prevalência de Helicobacter pylori e vírus Epstein-barr em crianças e adolescentes - OLIVEIRA, Kátia Soares de (Universidade Federal do Pará, 2013)
Introduction: Infections by Helicobacter pylori (HP) and Epstein-Barr virus (EBV) are common worldwide, although HP is the highest factor in gastroduodenal diseases, its percentage of association with EBV is uncertain. Both EBV and HP are classified are class 1 carcinogens by the World Health Organization, and a substantial number of individuals become co-infected in adulthood. These two pathogens may have synergic potential to cause perpetual chronic gastritis. The purpose of this paper was to verify the prevalence of HP and Epstein-Barr virus in children and adolescents. Material and Methods: Transversal descriptive study. The gastric mucosa of 64 children and adolescents was analyzed through the Urease Test to diagnose HP and the PCR technique to detect H. pylori’s cagA strain, the in situ hybridization technique to detect EBV and the pathological analysis to determine the histopathological characteristics. Results: The prevalence of HP and EBV found by this study was 53.1% and 3.1, respectively. Most of the patients infected by HP (94.3%) presented gastritis in the upper gastrointestinal endoscopy, with enanthemathous gastritis being the most commonly found type. In the histopathological analysis, most patients (97.1%) presented some level of gastritis, 80% of which classified as moderate chronic gastritis. Positive cagA strains were found in 64.7% of the patients infected with HP and all of them had gastritis, with predominance of moderate chronic gastritis (54%); however, there was no statistically significant correlation between these findings. There was also no statistically significant association between infection by HP and EBV in the studied population. The low prevalence of EBV in this analysis suggests that this virus is not an etiological agent in gastric mucosa lesions. To our knowledge, this is the first study that relates these two infectious agents in the gastric mucosa of children and adolescents in northern Brazil. Conclusion: Most of the findings in this study are in line with the literature; however, it is necessary to conduct larger studies, involving aimmunocompetent pediatric population in order to determine whether there is a correlation between infection by HP and EBV in our region.